Visual recovery after cataract surgery in children (2006)
Objective: To evaluate the visual outcome of cataract surgery in children aged 16 years and below at the University College Hospital (UCH), Ibadan. Methods: A retrospective review of the case records of patients aged 0-16 years who had cataract surgery at the UCH Ibadan between January 1995 and June 2006. Results: One hundred and fifty-one eyes of 101 patients were studied. Eighty-four eyes (55.6%) had congenital cataracts, 25.2% were developmental, while 13.9% were secondary to trauma. Seventy-one (70.3%) patients had bilateral cataracts. Eighty-nine (58.9%) of the eyes had an associated ocular pathology. Ninety-eight eyes (64.9%) had extracapsular cataract extraction without intraocular lens implant (ECCE), while 50 eyes (33.1 %) had extracapsular cataract extraction with posterior chamber intraocular lens implant (ECCE+PCIOL). Primary capsulotomy was performed on 34 eyes (22.5%). Postoperative complications were observed in 119 eyes (78.8%); with posterior capsule opacity occurring in 41.1%. Thirty-five eyes (38.9%) of those with objective visual acuity had a visual outcome ≥ 6/18. A visual outcome of 6/18 Dr better was significantly associated with increasing age (p =0.007) and the use of PCIOL implants (p =0.005), while poor visual outcome (≥ 6/24) was significantly associated with onset of cataract at birth (p =0.001); the presence of other ocular pathology (p =0.03); and a long delay between presentation and surgery (p= 0.02). Conclusion: The visual recovery of children who underwent cataract surgery in Ibadan is encouraging and the surgical results are likely to improve with increased proficiency in IOL implant surgery. The establishment of well-equipped and well-staffed paediatric ophthalmology centres would be beneficial in improving outcomes and would therefore help in achieving the goals of Vision 2020: The Right to Sight' .